2017
DOI: 10.2967/jnmt.117.197913
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 111In-Cl3 Scintigraphy for Differentiating Between Bone Marrow Reconversion and Bone Metastasis with Esophageal Adenocarcinoma

Abstract: Indium chloride (In-Cl) scintigraphy has been used to evaluate various hematological diseases for many years. However, there have been few reports on patients with bone marrow reconversion showing high uptake in In-Cl scintigraphy. Herein, we report a case of a 68-year-old man with esophageal cancer who underwent F-FDG PET/CT for staging of the disease.F-FDG PET/CT demonstrated high uptake in the first lumbar vertebral body, which was difficult to distinguish bone metastasis and bone marrow reconversion. In-Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In patients with malignancies, it is occasionally difficult to differentiate BMR from bone metastasis. Sporadic literatures reported BMR located in vertebrae (5)(6)(7)(8). For example, Okuda et al reported the MRI of a patient with esophageal adenocarcinoma showed patchy signal changes in the thoracic vertebral body, which mimicked bone metastases on MR (5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In patients with malignancies, it is occasionally difficult to differentiate BMR from bone metastasis. Sporadic literatures reported BMR located in vertebrae (5)(6)(7)(8). For example, Okuda et al reported the MRI of a patient with esophageal adenocarcinoma showed patchy signal changes in the thoracic vertebral body, which mimicked bone metastases on MR (5).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the patients with malignancies, it is occasionally difficult to differentiate BMR from bone metastasis, raising the risk of delayed or missed diagnoses. BMR located in some vertebrae of patients with malignant tumor mimicking bone metastases has been reported by sporadic literatures (5)(6)(7)(8). However, little literature reports BMR located in the pelvis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations